LENS OF LANGUAGE AND LITERATURE PROGRAMS IN THE NEW NORM EDUCATIONAL SETTING AMIDST PANDEMIC - Abarquez, Adrian (JET (Journal of English Teaching), 2021)
The current COVID-19 epidemic, which began in China and has nearly infected every nation globally, is one of the most recent public health catastrophes of worldwide significance. The language and literature programs in public and private schools have become more flexible due to the new standard structure that the Philippines adopted due to the Covid-19 epidemic. This study utilized a basic qualitative design under a qualitative research approach. There were six (6) English teachers as participants. The participants answered open-ended questions about language and literature programs in one's school in the new normal of education through social media platforms, Facebook messenger. The data has yielded three (3) themes: learning competencies and guides of language and literature programs, approaches and programs to language acquisition and literature appreciation, and new learning methods towards language and literature programs. Hence, the language programs sharpen students' macro abilities, which they will use in real-life situations. Literature programs also seek to help students understand and appreciate literary appreciation and analysis. The utilization of diverse techniques, programs, and competencies will allow for more practical learning. It is essential to the teacher's job that we motivate students to master these abilities. We scaffold them to help them comprehend our goal, which is to prioritize education for students to see what is unseen in the actual world.